Analisis Stabilitas Lereng Menggunakan Metode Fellenius Dan Metode Rankine Studi Kasus: Jln Poros Salu-Dende’ Lembang Salu Sarre Kecamatan Sopai - Yulius Pakiding; W Darma Putra; Marsel Sande (Departement of Mathematics Education, 2023)
The earth's surface has a fairly varied and irregular shape, consisting of high, low and water plains. As for the slopes, which are part of the highlands, because they are on the plateau, the slopes are an area where landslides often occur, this also does not escape the type of soil that is on the slopes, as happened on Jln. Salu-Dende axis Lembang Salu Sarre, Sopai District, where the landslide that occurred had an impact on the area because part of the road was also carried away by the landslide.To find out the cause of the landslide, an analysis was carried out at the landslide location, the analysis here was carried out by conducting soil research at the landslide location to determine the quality of the soil, the analysis was also carried out using 2 methods, namely the Fellenius method and the Rankine method to study further the condition of the landslide location so that it can determine the appropriate treatment.After conducting laboratory research, it was found that the soil at the landslide location was clay soil where clay soil had quite good adhesion between particles, and from the results of the analysis using the Fellenius method it was known that the FK value = 0,77 > 1,5 where the results were declared not safe. and from the results of the Rankine method analysis it is known that the value of Ka = 0.86 and Kp = 0.86 where these results are classified as cohesive soils, namely soils with high adhesion between particles. So that the countermeasures used are gabions, where gabions have elastic properties and are easy to apply. After carrying out a horizontal force analysis, the results obtained are ∑H = -0.7 < 0 and the results of the FS calculation = 1 where the results are declared safe.